Sosialisasi Perencanaan Keuangan Rumah Tangga Dalam Menghadapi Pandemik Covid-19 - Alfrida V.P. Yamanop; Yensawai E. Rumbiak; Yulita Gobai (Cenderabakti: Jurnal Pengabdian Kepada Masyarakat, 2022)
The service activity aims to help the group of housewives in the Rusunawa Koramil Hawai Sentani Complex -be ready and alert to face the COVID-19 pandemic. The method in this socialization activity is providing material, practical activities, and evaluating results. All participants were very enthusiastic and responded well to the socialization activities. participants said that this activity was good and helped them as housewives, especially for making family menus, so that family members did not get bored.